Parametric investigation on thermo-hydraulic performance of wire screen matrix packed solar air heater. (June 2015) - Verma, Prashant; Varshney, L.
Abstract: This paper presents performance results of a wire screen matrix packed solar air heater based on a mathematical model developed to investigate the effect of various system and operating parameters on the thermo-hydraulic performance. A computer programme is developed in C++ to estimate the temperature rise of the entering air for evaluation of effective efficiency by solving the governing equations numerically using relevant correlations for heat transfer coefficient for packed bed systems. The mathematical model developed is compared with the experimental results as well as previous model and the results are found fairly in agreement. Further, a correlation is developed for determination of extinction coefficient based on the geometrical parameter of matrix. Comparative study of thermo-hydraulic performance of high and low porosity matrices indicate the superiority of high porosity matrices as maximum effective efficiency for high porosity matrix is 76% while for low porosity it is found to be 50%, showing an overall enhancement of about 26%. The effective efficiency value clearly indicates that there exists an optimum duct depth (0.015–0.035 m), duct length (2–5 m) and width (0.2–0.6 m) which results in best thermo-hydraulic performance for various mass flow rates and the maximum effective efficiency is obtained for duct depth of 0.015 m, length 5 m and width 0.5 m.